2016
DOI: 10.1111/ane.12587
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with methylphenidate for fatigue after traumatic brain injury

Abstract: Individuals suffering from prolonged symptoms after TBI reported reduced mental fatigue and improved cognitive functions with long-term methylphenidate treatment. It is suggested that methylphenidate can be a treatment option for long-term mental fatigue and cognitive impairment after a TBI, but further randomized control research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…It found that methylphenidate reduces mental fatigue and improves cognitive functions with long-term methylphenidate treatment. [30] Although this study did not involve any type of control intervention, [30] its finding is consistent with the present study in showing that methylphenidate can reduce mental fatigue and improve cognitive outcomes in patients with TBI. Another reported study with a small sample size investigated the effects of methylphenidate and sertraline compared with placebo on various neuropsychiatric sequelae associated with TBI.…”
Section: Discussionsupporting
confidence: 88%
“…It found that methylphenidate reduces mental fatigue and improves cognitive functions with long-term methylphenidate treatment. [30] Although this study did not involve any type of control intervention, [30] its finding is consistent with the present study in showing that methylphenidate can reduce mental fatigue and improve cognitive outcomes in patients with TBI. Another reported study with a small sample size investigated the effects of methylphenidate and sertraline compared with placebo on various neuropsychiatric sequelae associated with TBI.…”
Section: Discussionsupporting
confidence: 88%
“…Our research group have found fatigue after TBI to be alleviated but not cured. This has been demonstrated in pharmacological studies with both methylphenidate (36,37) and a dopamine stabilizer OSU6162 (38), and also after a mindfulness intervention with the Mindfulness-Based Stress Reduction programme (MBSR) (39,40). However, a greater knowledge of the pathophysiological mechanisms underlying fatigue is needed as well as further information regarding the risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…aSAH occurs at a relatively young age and it is important to detect mental fatigue so that a patient may be able to return to work and other social activities. The rehabilitation needs to include education on how to use coping strategies, as well as offering and evaluating pharmacological treatment in order to perceive the highest possible quality of life (Johansson, Wentzel, Andréll, Rönnbäck, & Mannheimer, ). In this study, we found a correlation between the GOSE and the MFS scale.…”
Section: Discussionmentioning
confidence: 99%